Efektifitas Permainan Ka-Gem dalam Meningkatkan Pengetahuan Mitigasi Bencana pada Anak Kelas 5 SD - Syifa Aryani; Devi Lusiria (Jurnal Ilmiah Literasi Indonesia, 2026)
Indonesia, including Padang City, is highly prone to earthquakes, yet disaster mitigation awareness among elementary students remains limited. This study evaluates the effectiveness of Ka-Gem, an educational card game, in enhancing fifth-grade students’ knowledge of disaster mitigation. Employing a quantitative one-group pretest-posttest design, the study involved 20 students from SDN 29 Dadok Tunggul Hitam. Data were collected through tests administered before and after gameplay and analyzed using a paired sample t-test. Findings revealed a significant improvement in students’ understanding (p < 0.001), suggesting that Ka-Gem fosters active, enjoyable, and meaningful learning. The game's interactive format and visual content supported better retention of mitigation strategies. These results highlight the potential of game-based learning as a tool for disaster education in primary schools.